The interplay between ADHD and school shift on educational outcomes in children and adolescents: a cross-sectional and longitudinal analysis. - Porto, Ighor Miron; do Amaral, João Villanova; Pacheco, João Pedro Gonçalves; Terra, Igor; Miguel, Euripedes Constantino; Pan, Pedro Mario; Gadelha, Ary; Rohde, Luis Augusto; Salum, Giovanni Abrahão; Hoffmann, Maurício Scopel (European Child & Adolescent Psychiatry, 2025)
Many countries implement double-shift schooling systems, offering morning or afternoon shifts. Given attention-deficit/hyperactivity disorder (ADHD) is associated with circadian preference for eveningness, this study hypothesised that young people with ADHD would have worse educational performance than those without ADHD, particularly when attending school in the morning shift. Data were drawn from a Brazilian school-based cohort (n = 2,240, 6–14 years old, 45.6% female; 50.2% in the morning shift; 11.2% with ADHD). ADHD was determined by child psychiatrists using semi-structured interview. Educational outcomes were measured cross-sectionally and three years later (80% retention), including standardised performance test of reading and writing (primary outcome), and parent-reported performance in school subjects and negative school events (repetition, suspension, or dropout). Regression models, adjusted for demographic and cognitive factors, tested the hypotheses, with sensitivity analyses using continuous ADHD symptom measures. Attrition was addressed with inverse probability weighting. ADHD and morning shift were associated with lower reading and writing ability and with higher odds for negative school events cross-sectionally. ADHD predicted lower performance in school subjects and higher negative school events longitudinally. Contrary to our hypothesis, interaction was observed only cross-sectionally, indicating that ADHD symptoms were positively associated with the primary outcomes only in the afternoon shift. Morning shift performance remained consistently low regardless of ADHD symptom levels. These findings suggest that while studying in the afternoon shift benefits children with lower attentional problems, the morning shift does not exacerbate educational difficulties for those with ADHD or higher ADHD symptoms.